The design and synthesis of super reducing organic photocatalysts through mechanistic understanding with application towards unactivated arene activation - Green, Alexander Richard, author; Miyake, Garret, advisor; Paton, Robert, committee member; Bailey, Travis, committee member; Reisfeld, Brad, committee member (Colorado State University. Libraries, 2024)
The work described in this dissertation focuses on the understanding of an organic photocatalyst system through a degradation and mechanistic study, leading to development of a new class of organic photocatalyst and improved application. The design of new organic photocatalysts is crucial for eliminating the need to use rare and expensive ruthenium and iridium that have dominated the field of photoredox catalysis for the past decade. Additionally, most of the catalysts describe here-in operate through a unique two electron, one proton activation mechanism to generate a closed shell species which enables direct quenching towards unactivated arenes such as benzene, without the use of a stoichiometric amount of reductant such as solvated electrons coming from pyrophoric metals. The progress described within this dissertation provides a deeper understanding of tunable organic reductants and their function.
Keywords: hydrocarbons; photochemistry; aromatic compounds; redox reactions; photocatalysis